Tumor suppressing role of serum-derived exosomal microRNA-15a in osteosarcoma cells through the GATA binding protein 2/murine double minute 2 axis and the p53 signaling pathway. Issue 1 (1st January 2021) - Wu, Chunyu; Li, Zhigang; Feng, Guang; Wang, Liqin; Xie, Jingri; Jin, Yang; Wang, Long; Liu, Songjiang
ABSTRACT: Exosomes are emerging tools for transporting lipids, proteins, microRNAs (miRNAs), or other biomarkers for clinical purposes. They have produced widespread concern in managing human diseases, including osteosarcoma (OS). This study focuses on the function of serum-derived exosomal miR-15a in the growth of OS cells and the mechanism of action. Differentially expressed genes between OS and normal samples were screened using two datasets GSE70367 and GSE65071. miR-15a was poorly expressed, whereas GATA-binding protein 2 (GATA2) and murine double minute 2 (MDM2) were abundantly expressed in OS samples. miR-15a and its target mRNAs, including GATA2, were enriched in the p53 signaling pathway. miR-15a directly targets GATA2 mRNA to inhibit its expression, whereas GATA2 activates the transcription of MDM2, a negative regulator of p53. Overexpression of GATA2 and MDM2 promoted proliferation and cell cycle progression of MG-63 cells, whereas miR-15a blocked this axis and suppressed cell growth. miR-15a was identified as a major cargo of serum-derived exosomes, and exosomes conveying miR-15a were internalized by OS cells. This study demonstrated that miR-15a suppresses the GATA2/MDM2 axis to inhibit the proliferation and invasiveness of OS cells in vitro through the p53 signaling pathway.